Babies born at the threshold of viability: changes in survival and workload over 20 years. Issue 1 (19th April 2012) - Seaton, Sarah E; King, Sophie; Manktelow, Bradley N; Draper, Elizabeth S; Field, David J
Abstract : Objective: To assess the care given to the babies born at the threshold of viability over the last 20 years using regional and national data. Design: Population-based retrospective study. Setting: Former 'Trent' health region. Participants: Babies born between 1 January 1991 and 31 December 2010 at 22 +0 to 25 +6 weeks gestational age. Main outcome measure: Survival and use of respiratory support. Methods: Data of all babies born between 1 January 1991 and 31 December 2010 with a gestational age of 22 +0 to 25 +6 weeks and admitted to a neonatal unit were extracted from The Neonatal Survey. Use of respiratory support in terms of ventilation and continuous positive airway pressure (CPAP) for this group of babies was calculated as a proportion of the total used by the whole neonatal intensive care population within the defined study area. Results: The proportion of babies surviving to discharge increased significantly over time in those born at 24 and 25 weeks (p<0.01) but failed to achieve statistical significance for those at 23 weeks (p=0.08). No babies born at 22 weeks survived. The babies born at 22–25 weeks accounted for 26.3% of all ventilation and 21.5% of CPAP given. Conclusion: Our work concurs with the current UK guidelines. There could be advantages in focusing the care of babies born at 23 weeks to a small number of intensive care units to allow specialist expertise to develop in all aspects of the management of these babies. However, focusing care will not necessarily improve survival or reduce morbidity.